SARS‐CoV‐2 and wastewater: What does it mean for non‐human primates?. Issue 4 (18th October 2021) - Mathavarajah, Sabateeshan; Melin, Amanda; Dellaire, Graham
Abstract: In most of our lifetimes, we have not faced a global pandemic such as the novel coronavirus disease 2019. The world has changed as a result. However, it is not only humans who are affected by a pandemic of this scale. Our closest relatives, the non‐human primates (NHPs) who encounter researchers, sanctuary/zoo employees, and tourists, are also potentially at risk of contracting the virus from humans due to similar genetic susceptibility. "Anthropozoonosis"—the transmission of diseases from humans to other species—has occurred historically, resulting in infection of NHPs with human pathogens that have led to disastrous outbreaks. Recent studies have assessed the susceptibility of NHPs and predict that catarrhine primates and some lemurs are potentially highly susceptible to infection by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) virus. There is accumulating evidence that a new factor to consider with the spread of the virus is fecal‐oral transmission. The virus has been detected in the watersheds of countries with underdeveloped infrastructure where raw sewage enters the environment directly without processing. This may expose NHPs, and other animals, to SARS‐CoV‐2 through wastewater contact. Here, we address these concerns and discuss recent evidence. Overall, we suggest that the risk of transmission of SARS‐CoV‐2 via wastewater is low. Nonetheless, tracking of viral RNA in wastewater does provide a unique testing approach to help protect NHPs at zoos and wildlife sanctuaries. A One Health approach going forward is perhaps the best way to protect these animals from a novel virus, the same way that we would protect ourselves. Abstract : Non‐human primates (NHPs) are at risk of contracting of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). A One Health approach through the monitoring of wastewater for viral RNA protects not only NHPs but our communities. Research highlights: Risk of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spillover in non‐human primate (NHP) populations is low from wastewater contamination of natural waterways. Synanthropic primates are a high‐risk group for viral pathogen spillover. Wastewater monitoring allows for early detection of the virus at zoos and wildlife sanctuaries to protect species.